Fluent Numerical Study of Lifting Resistance and Wave Impact Height of a Cross-Sea Bridge Based on Cloud Computing - Jun Hu; Jiayu Yu (Advances in Civil Engineering)
Due to the relationship between the elevation of the roads on both sides of the strait and the adjustment with the surrounding landscape, the elevation of the deck of the bridge is restricted when the bridge is designed. When the water level rises below the superstructure of the sea-crossing bridge, the main guardrail of the bridge may be partially or completely submerged in the water, and the superstructure of the bridge is affected by huge waves, which threatens the safety of the bridge. Based on cloud computing technology, this paper establishes a digital model of the crossing bridge and monitors the specific state of the bridge through the simulation of the bridge, collects various data of the bridge, analyzes the dataset, and analyzes the crossing bridge. This paper analyzes the correlation between the magnitude of the wave force and the height of the wave impact on the bridge superstructure and studies the relationship between the lift resistance coefficient and the impact height. The analysis of the lift coefficient and drag coefficient of different water depths in the case of 20-year operation shows that the height of the main beam where the large wave force acts has two values, 2.0 and 3.0 m in the case of 20-year operation; in case of 50-year working conditions, it is 2.5 and 3.0 m; in case of 100-year working conditions, the lift coefficient is 1.5 and 3.5 m, and the resistance coefficient is 2.0 and 3.5 m. Under the three water depth wave conditions, the fluctuation range of the lifting resistance curve is large when the water level depth is 10 m. Once a large wave occurs, the wave will not spread well due to the shallow current, which will cause a large wave force impact on the bridge. Therefore, when choosing a bridge, it is not recommended to build under a water depth of about 10 m. Optimizing the design of the main beam according to the analysis results of this paper will help to improve the ability of the bridge main beam to resist wave loading and provide a reference for seeking effective measures to reduce the impact of waves.